One way or another? An international comparison of expatriate performance management in multinational companies. Issue 5 (16th June 2021) - Bader, Anna Katharina; Bader, Benjamin; Froese, Fabian Jintae; Sekiguchi, Tomoki
Abstract: Due to the high costs and strategic importance of expatriate assignments, expatriate performance management (EPM) plays an increasingly important role for multinational enterprises (MNEs). However, research on EPM is still in its infancy. Drawing from the convergence/divergence debate in international human resource management, this study investigates and compares EPM strategies and practices across MNEs from three different country clusters to better understand whether EPM practices tend to converge, diverge, or crossverge (i.e., show aspects of both). Results from surveying 132 Anglo‐Saxon, Germanic, and Japanese MNEs reveal prominent differences (divergence) at the EPM strategic level such that Japanese MNEs tend to pursue more ethnocentric staffing strategies and design EPM systems specifically tailored to expatriates. On the practice level, we found both commonalities and differences between Japanese and Anglo‐Saxon and Germanic MNEs, pointing toward crossvergence. Theoretical and practical implications of our results are discussed.